Pendampingan Pemanfaatan Tajug sebagai Media Peningkatan Minat Baca di Kampung Pasir Desa Cikeris - Santi Aprilia; Solihah Bagus; Usep Setiawan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Technological development has brought significant changes to education, including efforts to improve reading literacy. However, children’s reading interest in Kampung Pasir, Cikeris Village remains low due to limited literacy facilities. This community service program aims to assist the community in utilizing the tajug as a medium to increase children’s reading interest. The method applied was Participatory Action Research (PAR) through planning, action, observation, and reflection stages. The program was implemented by organizing the tajug space, providing reading materials, conducting literacy socialization, and holding group reading activities. The results indicate increased enthusiasm among children to visit and read in the tajug and higher participation in literacy activities. This program shows that the tajug can function not only as a place of worship but also as an educational space that supports community literacy culture.